Introduction: Tangled Matters - CATHERINE KELLER; MARY-JANE RUBENSTEIN (Entangled Worlds, 2017)
It is not just that we are entangled in matter—we subjects who read, write, and ruminate on what “we” are. We are materializations entangled in other materializations; we happen in our mattering. What matters in our ethics, our politics, our worlds entangles us in and as new materializations. And at this juncture, it entangles scholarship in retrievals and rethinkings of matter itself. Even disciplines that struggle with long histories of disembodied transcendence are registering the effects. The “new materialisms” currently coursing through cultural, feminist, political, and queer theories seek to displace human privilege by attending to the agency of